ANALYZING SOMATOTYPE PROFILES AND PHYSICAL VARIABLES AMONG COLLEGE STUDENTS: A COMPREHENSIVE STUDY - NAGANNA M.S; Dr. R. RAMAKRISHNAN (The Bioscan, 2024)
This study aims to analyze the relationship between somatotype profiles and physical performance variables among college students. Utilizing a stratified sampling method, 150 male students aged 18 to 23 years from Mysore University affiliated colleges in Mysore, Karnataka, India, were selected. The sample was stratified based on academic disciplines to ensure a representative distribution reflecting diverse physical activity levels and body compositions across different fields of study. Participants were categorized into three somatotype groups: Mesomorphs, Ectomorphs, and Endomorphs. The primary criterion variables assessed were abdominal strength and flexibility. Abdominal strength was measured using the Sit-ups test, while flexibility was evaluated with the Sit and Reach test. Data analysis employed ANCOVA to compare mean differences in abdominal strength and flexibility among the three somatotype groups. Scheffe's post hoc test was utilized for pairwise comparisons when significant differences were detected. The results revealed significant effects of body type on both abdominal strength and flexibility. Mesomorphs consistently exhibited higher levels of abdominal strength and flexibility compared to Ectomorphs and Endomorphs. These findings align with existing research, highlighting the influence of body composition on physical performance outcomes. The superior performance of Mesomorphs is attributed to their muscular build and balanced muscle distribution. In contrast, Ectomorphs and Endomorphs displayed lower performance, emphasizing the variability in physical capabilities associated with different body types. This study aims to analyze the relationship between somatotype profiles and physical performance variables among college students. Utilizing a stratified sampling method, 150 male students aged 18 to 23 years from Mysore University affiliated colleges in Mysore, Karnataka, India, were selected. The sample was stratified based on academic disciplines to ensure a representative distribution reflecting diverse physical activity levels and body compositions across different fields of study. Participants were categorized into three somatotype groups: Mesomorphs, Ectomorphs, and Endomorphs. The primary criterion variables assessed were abdominal strength and flexibility. Abdominal strength was measured using the Sit-ups test, while flexibility was evaluated with the Sit and Reach test. Data analysis employed ANCOVA to compare mean differences in abdominal strength and flexibility among the three somatotype groups. Scheffe's post hoc test was utilized for pairwise comparisons when significant differences were detected. The results revealed significant effects of body type on both abdominal strength and flexibility. Mesomorphs consistently exhibited higher levels of abdominal strength and flexibility compared to Ectomorphs and Endomorphs. These findings align with existing research, highlighting the influence of body composition on physical performance outcomes. The superior performance of Mesomorphs is attributed to their muscular build and balanced muscle distribution. In contrast, Ectomorphs and Endomorphs displayed lower performance, emphasizing the variability in physical capabilities associated with different body types.